Early stages of high-temperature oxidation of Ni- and Co-base model superalloys: A comparative study using rapid thermal annealing and advanced electron microscopy - Kubacka, Dorota; Weiser, Martin; Spiecker, Erdmann (Corrosion Science, 2021)
A novel approach based on rapid thermal annealing and advanced electron microscopy is used to elucidate the differences in early stages of high-temperature oxidation of Ni- and Co-base superalloys at 900 °C. STEM-EDX results obtained for two model superalloys with exactly the same alloying additions demonstrate the individual role of the γ and γ’ phase during initial oxidation. Observed differences in Al2O3 formation can be directly correlated to changes in the partitioning behavior and the type of defects introduced during oxidation, depending on the base element. Explanations for the worse oxidation resistance of γ’-strengthened Co-base superalloys are proposed.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Co/Ni-base superalloys; Diffusion; High-temperature oxidation; Initial oxidation; STEM